Revealing isomerism in sodium-water clusters: Photoionization spectra of Na(H2O)n (n = 2-90) - Dierking, Christoph W; Zurheide, Florian; Zeuch, Thomas; Med, Jakub; Parez, Stanislav; Slavíček, Petr (The Journal of chemical physics, 2017)
Soft ionization of sodium tagged polar clusters is increasingly used as a powerful technique for sizing and characterization of small aerosols with possible application, e.g., in atmospheric chemistry or combustion science. Understanding the structure and photoionization of the sodium doped clusters is critical for such applications. In this work, we report on measurements of photoionization spectra for sodium doped water clusters containing 2-90 water molecules. While most of the previous studies focused on the ionization threshold of the Na(H2O)n clusters, we provide for the first time full photoionization spectra, including the high-energy region, which are used as reference for a comparison with theory. As reported in previous work, we have seen an initial drop of the appearance ionization energy with cluster size to values of about 3.2 eV for n<5. In the size range from n = 5 to n = 15, broad ion yield curves emerge; for larger clusters, a constant range between signal appearance (∼2.8 eV) and signal saturation (∼4.1 eV) has been observed. The measurements are interpreted with ab initio calculations and ab initio molecular dynamics simulations for selected cluster sizes (n≤ 15). The simulations revealed theory shortfalls when aiming at quantitative agreement but allowed us identifying structural motifs consistent with the observed ionization energy distributions. We found a decrease in the ionization energy with increasing coordination of the Na atom and increasing delocalization of the Na 3s electron cloud. The appearance ionization energy is determined by isomers with fully solvated sodium and a highly delocalized electron cloud, while both fully and incompletely solvated isomers with localized electron clouds can contribute to the high energy part of the photoionization spectrum. Simulations at elevated temperatures show an increased abundance of isomers with low ionization energies, an entropic effect enabling size selective infrared action spectroscopy, based on near threshold photoionization of Na(H2O)n clusters. In addition, simulations of the sodium pick-up process were carried out to study the gradual formation of the hydrated electron which is the basis of the sodium-tagging sizing.